Temperature-driven variation in the removal of heavy metals from contaminated tailings leaching in northern Norway - Fu, Shuai; Lu, Jinmei (Environmental Monitoring and Assessment, 2019)
High amounts of tailings with a low recycling rate are generated during mining and smelting processes, and a lot of environmental problems were caused by heavy metal leaching from tailings. Temperature is a key point in heavy metals leaching, and knowing the effects of temperature on tailings leaching is useful for tailings management. A small-scale batch leaching experiment was conducted at different temperatures to test temperature-driven heavy metal leaching from tailings in the arctic area. The variation in the leaching of heavy metals from tailings was investigated by a small-scale batch leaching experiment. Results showed that 10 °C is a threshold temperature for the leaching activity of the tested elements. Fe, Cr, and Cu are significantly correlated with temperature in the leaching. Leaching rates of Cr, Cu, and Ni increase as temperature rises. Leaching rates of Cr, Cu, Ni, V, and Zn change by a polynomial model with temperatures, whereas that of Fe changes with a linear model. V shows an antagonistic relationship with Cu, Fe, and Ni in the leaching. However, Cu, Cr, Ni, and Fe show a synergistic relationship. Discovering the threshold temperature of leaching tailings in the arctic area and concluding the influence factors and the relationship between heavy metals leaching and temperature are useful for tailings management.